Matrix reloaded - Silver, Joel.; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Fishburne, Laurence, III, 1961-; Reeves, Keanu; Smith, Jada Pinkett, 1971-; Foster, Gloria, 1936-2001.; Kilde, David; Bernhardt, Daniel; Bellucci, Monica, 1968-; Bliss, Ian.; Cotter, Paul.; et al. (Burbank, CA Warner Home Video, 2003)
Neo, Trinity, and Morpheus continue to lead the revolt against the Machine Army. In their quest to save the human race from extinction, they gain greater insight into the construction of The Matrix and Neo's pivotal role in the fate of mankind.
Matrix reloaded
Originally released as a motion picture in 2003.
Special features: the MTV Movie Awards Reloaded; documentaries: "Preload": go behind the scenes with the cast and crew, "The freeway chase": anatomy of the mind-blowing scene, "Enter the Matrix": making of the ground-breaking video game, "What is the animatrix?", "The Matrix unfolds: a look at the Matrix phenomenon, "Get me an exit": Matrix-inspired design advertising; DVD-ROM features: Web links to the official Matrix website.
Directors Andy & Larry Wachowski ; director of photography, Bill Pope ; editor, Zach Staenberg ; music, Don Davis ; costume designer, Kym Barrett ; production designer, Owen Paterson ; visual effects, Yakov Baytler [and others] ; special effects supervisor, Steve Courtley.
Laurence Fishburne, Keanu Reeves, Jada Pinkett Smith, Gloria Foster, David Kilde, Daniel Bernhardt, Monica Bellucci, Ian Bliss, Paul Cotter, Matt McColm.
MPAA rating: R; for sc-fi violence and some sexuality.
Closed-captioned.
Keywords: Human beings -- Drama; Artificial intelligence -- Drama; Feature films; Science fiction films; Drama; Dystopian films; Feature films; Fiction films; Science fiction films; Video recordings for the hearing impaired; Feature films -- Australia